IMPLEMENTASI LAPORAN KEUANGAN WARALABA DI INDONESIA - Nawaal Fakhri Widiantoro; Endah Susilowati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research highlights the importance of preparing accurate and transparent financial statements in managing franchise businesses for performance monitoring, transparency, and informed decision-making. A transparent franchise offering prospectus is necessary for feasibility studies and fair agreements between franchisors and franchisees. Case studies conducted in previous research show that profit planning and cost-volume-profit (CVP) analysis help achieve profit targets and avoid losses. Strategic management analysis also highlights effectiveness in developing business opportunities, as well as supporting company growth and sustainability. The preparation of financial statements for business partners enhances the efficiency of financial monitoring. These findings underscore the importance of effective financial reporting and strategic management in franchise businesses.